“Caracterización preliminar morgológica y de reproductividad de 42 genotipós promisorios de cacao (theobroma cacao L.) colectados en la cuenca del huallaga San Martín” - Bartra Perea, José Miguel (2009)
This research is part of the effort of the lnstitute of Tropical Cr0ps, which seeks -to develop superior genotypes in cacao. The study was conducted between February 2008 to January 2009 and consisted of the evaluation of 42 cocoa clones under fieid condfüons, which were previously selected areas and Tocache Juanjuí on farmers' fields, taking favorable characteristics into account productivity and resistance to pests and diseases, the objective was to determine the phenotypic characteristics of 42 genotypes of cacao, coHected -in the Huallaga Basin - San Martín, the methodology was the use of a list of descriptors developed by the lnternational Cocoa-Germplasm Database The genetic material consisted of clones from the Huallaga River, was not used any experimental design and during the study were assessed quantitative and qualitative descriptors of the plant, leaf, flower, fruit and seeds. Genetic variability was found in the clones studied, both quantitative and qualitative characters in vegetativa and reproductiva organs. We conclude that the use of parameters morfofisiológicos allowed to accumulate a large amount of new information on pre-selected genotypes, distinguished phenotypically materials and have more elements to select the most outstanding -materiais for inclusion in the next phases of the Program of Genetic lmprovenieht lnstitute of Tropical Crops.